Development of A Thinking Working Scaffolding Sharing Model Based on Local Wisdom For 21st Century Learning - Desi Ratna Ayu; Syihabudin Syihabudin; Isah Cahyani; Khaerudin Kurniawan; Dedi Irawan; Siti Maryam Maulida (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2025)
The purpose of this study was to develop a Thinking Working Scaffolding Sharing Model based on local wisdom of the principles of silih asah, silih asih, silih asuh in learning to write commercial posters related to the Indonesian creative economy for junior high school/Islamic junior high school students. The research method used is the research and development (R&D) with the ADDIE model. The results of the study showed that students need a process of interaction and communication in learning. The validation results of the development of the Thinking Working Scaffolding Sharing model based on local wisdom have a model assessment percentage of 98.3%, media materials of 91.7%, evaluation of 96.7%, the development of this model is categorized as